Characterization of Fly Ash Catalyst Using XRD Method for Biofuel Production from Used Cooking Oil - Dina Eka Pranata; Aida Syarif; Muhammad Yerizam (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
Fly ash catalyst that has been activated using NaoH 2M was analyzed using XRD at an angle of 2θ = 15 ° - 80 ° with a wavelength (λ) of X rays of 0.15406 nm. From the results of the analysis, the NaO26Si6Y9 compound is obtained with a hexagonal structure. Furthermore, the XRD analysis results obtained in the form of wavelength, intensity, 2θ and FWHM values will be substituted into the Debye Scherrer equation to calculate the size of the crystal structure of the Fly Ash catalyst. From this equation, a graph of the relationship between ln(b) dan ln(1/cos(q ))  will be drawn so that the intercept value is - 4.0688 and the value of K = 0.9 and λ = 0.15406 nm. The value of K and λ can be calculated using the modified Debye Scherrer equation, so that the crystal size (D) is 8,10942 nm.